Dobrodziejstwa i pułapki tożsamości - Zygmunt Bauman (Jesuit University Ignatianum in Krakow, 2017)
The question about identity has recently become more important than it used to be in the past. Never before has the world been changing so quickly; never before have the individuals and societies been faced with a question about the sense of their own existence, about an invariable point of reference for the hasty course of history. What makes these questions even more difficult is the fact that they consist of two interdependent strings. The first one constitutes the aspiration for one's own individual allotment of rules and destinations. The second one comprises discovering aspirations and expectations of the environment, investigating the roommates or neighbours of our own individual identity. The author does not offer a clear-cut prescription for identity problems. Nevertheless, he attempts to show the comfortable and secure mode of life of a traditionalist from the past - free from ideological choices between conservatism and modernism - for whom, the world remained invariable and stable. Since in that world everything had its own fixed place, identity could not be threatened in any way. The situation, however, appears opposite in the world where nothing is stable or definite: also individual identity cannot be fixed permanently. The author quotes concepts of two 20th century ethical philosophers, Emmanuel Levinas and Knud Lrgstrup, who claimed that the contemporary question "who am I" and "how do I differ from others", should be replaced with the search for the answer to the query "who am I for other people" and "what do I mean to them". According to the aforementioned philosophers this is how the ethical sense of the identity problem shows itself at present. The author seems to share this opinion, however he does not provide a definite answer. Instead, he states that in contemporary world identity is not given to us, but it is rather assigned; realising the meaning of "we" for each of us requires continuous effort - "this effort incessantly gives rise to human community as well as human self", the author